Varicella pneumonia in a patient with AIDS - Díaz-Rodríguez, Priscila Milagros (2022)
We present the case of a 21-year-old male with a history of HIV/AIDS without antiretroviral treatment and no history of having suffered from chickenpoxor having been vaccinated, who developed dermal chickenpox lesions and presented bilateral and diffuse micronodules and hypoxemia on the chest x-ray.Chickenpox pneumonia with respiratory failure was diagnosed as a primary infection, and the response to intravenous acyclovir and oxygen therapy was favorable.